Community-based psychosocial substance use disorder interventions in low-and-middle-income countries: a narrative literature review - Jan Manuel Heijdra Suasnabar (International Journal of Mental Health Systems, 2020)
Abstract Background Mental health and substance use disorders (SUDs) are the world’s leading cause of years lived with disability; in low-and-middle income countries (LIMCs), the treatment gap for SUDs is at least 75%. LMICs face significant structural, resource, political, and sociocultural barriers to scale-up SUD services in community settings. Aim This article aims to identify and describe the different types and characteristics of psychosocial community-based SUD interventions in LMICs, and describe what context-specific factors (policy, resource, sociocultural) may influence such interventions in their design, implementation, and/or outcomes. Methods A narrative literature review was conducted to identify and discuss community-based SUD intervention studies from LMICs. Articles were identified via a search for abstracts on the MEDLINE, Academic Search Complete, and PsycINFO databases. A preliminary synthesis of findings was developed, which included a description of the study characteristics (such as setting, intervention, population, target SUD, etc.); thereafter, a thematic analysis was conducted to describe the themes related to the aims of this review. Results Fifteen intervention studies were included out of 908 abstracts screened. The characteristics of the included interventions varied considerably. Most of the psychosocial interventions were brief interventions. Approximately two thirds of the interventions were delivered by trained lay healthcare workers. Nearly half of the interventions targeted SUDs in addition to other health priorities (HIV, tuberculosis, intimate partner violence). All of the interventions were implemented in middle income countries (i.e. none in low-income countries). The political, resource, and/or sociocultural factors that influenced the interventions are discussed, although findings were significantly limited across studies. Conclusion Despite this review’s limitations, its findings present relevant considerations for future SUD intervention developers, researchers, and decision-makers with regards to planning, implementing and adapting community-based SUD interventions.